2014
DOI: 10.1155/2014/893836
|View full text |Cite
|
Sign up to set email alerts
|

Piriformis Syndrome in Fibromyalgia: Clinical Diagnosis and Successful Treatment

Abstract: Piriformis syndrome is an underdiagnosed extraspinal association of sciatica. Patients usually complain of deep seated gluteal pain. In severe cases the clinical features of piriformis syndrome are primarily due to spasm of the piriformis muscle and irritation of the underlying sciatic nerve but this mysterious clinical scenario is also described in lumbar spinal canal stenosis, leg length discrepancy, piriformis myofascial pain syndrome, following vaginal delivery, and anomalous piriformis muscle or sciatic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Based on the Michel clinical scoring system, iTh and iCSA are excellent parameters for differentiating between stage 2 and stage 3 PS and between normal and all-stage PS patients. Our results are similar to those of Siddiq et al, 19,20 who found that piriformis muscle thickness increased, but did not describe CSA.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the Michel clinical scoring system, iTh and iCSA are excellent parameters for differentiating between stage 2 and stage 3 PS and between normal and all-stage PS patients. Our results are similar to those of Siddiq et al, 19,20 who found that piriformis muscle thickness increased, but did not describe CSA.…”
Section: Discussionsupporting
confidence: 92%
“…I advised them to continue with piriformis muscle stretching exercises. Fortunately, none of our study subjects developed features that matched with central sensitization, namely fibromyalgia, irritable bowel syndrome, etc ., nonetheless reported to be possible if persistent somatic pain left untreated or poorly managed as had been demonstrated in one of my previous studies [ 13 ].…”
Section: Discussionmentioning
confidence: 96%
“…Here, wallet neuritis diagnosis was straightforward; nevertheless, most often it can be confused with clinical conditions of several low back pain generators like facet joint (lumbar facet arthropathy), sacroiliac joint (sacroiliac joint dysfunction), lumbar spinal canal (stenosis), piriformis muscle (piriformis syndrome), ischial bursa (bursitis), auricular part of ilium (osteitis condensans illi), hip joint (hip arthropathy), hamstring muscle origin (hamstring muscle rupture), etc [ 3 , 10 , 13 ]. Most importantly, we were cautious about them during patients’ screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ACR 1990 classification criteria for Fibromyalgia syndrome (FMS), one of the 18 tender areas resides at the insertion of PM tendon to the posterior aspect of greater trochanter of the femur that could get irritated depending on the risk factors causing more gluteal pain or persistent regional gluteal pain. Because of inappropriately treated PS could induce the development of central sensitization which may result in generalized body ache, for example FMS [8,9].…”
Section: Editorial Piriformis Syndrome: Still Unsolved Issuesmentioning
confidence: 99%